The antitumor effect induced by an IL-2 ‘no-alpha’ mutein depends on changes in the CD8+ T lymphocyte/Treg cell balance - Carmenate, Tania; Montalvo, Galia; Lozada, Sum Lai; Rodriguez, Yaretnis; Ortiz, Yaquelin; Díaz, Claudia; Avellanet, Janet; Kim, Juhee; Surh, Charles D.; Graça, Luis; León, Kalet (Frontiers in Immunology, 2022)
High doses of interleukin-2 (IL-2) have been used for the treatment of melanoma and renal cell carcinoma, but this therapy has limited efficacy, with a ~15% response rate. Remarkably, 7%–9% of patients achieve complete or long-lasting responses. Many patients treated with IL-2 experienced an expansion of regulatory T cells (Tregs), specifically the expansion of ICOS+ highly suppressive Tregs, which correlate with worse clinical outcomes. This partial efficacy together with the high toxicity associated with the therapy has limited the use of IL-2-based therapy. Taking into account the understanding of IL-2 structure, signaling, and in vivo functions, some efforts to improve the cytokine properties are currently under study. In previous work, we described an IL-2 mutein with higher antitumor activity and less toxicity than wtIL-2. Mutein was in silico designed for losing the binding capacity to CD25 and for preferential stimulation of effector cells CD8+ and NK cells but not Tregs. Mutein induces a higher anti-metastatic effect than wtIL-2, but the extent of the in vivo antitumor activity was still unexplored. In this work, it is shown that mutein induces a strong antitumor effect on four primary tumor models, being effective even in those models where wtIL-2 does not work. Furthermore, mutein can change the in vivo balance between Tregs and T CD8+ memory/activated cells toward immune activation, in both healthy and tumor-bearing mice. This change reaches the tumor microenvironment and seems to be the major explanation for mutein efficacy in vivo.